Decision Support System for Selection of Suitable Mariculture Site in the Western Part of Java Sea, Indonesia - W. Windupranata; R. Mayerle (Institute for Research and Community Services, Institut Teknologi Bandung, 2009)
Mariculture (marine aquaculture) has been intensified and has created essential employment opportunities over the last two-decades in Indonesia, as well as many other countries in the world. This development has negative impact to the environment. Considerable amounts of nutrient waste in dissolved and particulate form were released by intensive fish farming into the environment through feed excess, soluble fish excretion and faeces production. One of the first steps to avoid the dangerous environmental impacts is careful site selection to minimize environmental impacts arising from the farming activities (sustainability) as well as to guarantee adequate conditions from the operational point of view (suitability).The paper focuses on the development of a Decision Support System (DSS) as a tool for the appropriate selection of mariculture site location. The DSS is based on physical, chemical and sediment criteria as well as on data of conflicting coastal use. The GIS analysis results in a map indicating the suitable areas for the improved method of offshore cage mariculture. In this study, emphasis was placed on finfish species; however the methods and results may be employed for other species as well following some modifications.The DSS was applied for the western part of Java Sea, Indonesia. The data were acquired from direct field measurement, numerical modeling and existing information from particular agencies. Numerical modeling was used to obtain spatial and temporal distributions of hydrodynamic parameters (i.e. current velocities and water levels). The Delft3D modeling system (Delft Hydraulics, The Netherlands) was employed for this purpose. The DSS was developed under GIS application of ESRI® ArcGISâ„¢ using weighted overlay method. The results showed the adequacy of the system for supporting governmental authorities in the implementation, environmental controlling, and estimation of overall carrying capacity for environmental sustainable marine fish farming.